2021
DOI: 10.1111/jir.12911
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurring medical and behavioural conditions in children with Down syndrome with or without ADHD symptom presentation

Abstract: Background Co‐occurring attention deficit hyperactivity disorder (ADHD) is a challenge to characterise in the presence of other medical conditions commonly present in children with Down syndrome (DS). The current study examined differences among children with DS with or without ADHD symptomatology in terms of demographics, developmental level, co‐occurring medical conditions, and parent and teacher ratings of behaviour and executive functioning. Methods Parents and teachers of 108 school‐age children with DS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
6
2
Order By: Relevance
“…Past studies on sleep and feeding issues also differ from our findings. Unlike previous reports that individuals with DS and other ND conditions like ASD, ADHD, and oppositional defiant disorder have high rates of sleep and feeding problems (Dinkler et al, 2022; Esbensen et al, 2022; Fuemmeler et al, 2020; Reynolds et al, 2019), we did not find significantly higher odds of these issues in our participants with co‐occurring ND and MH conditions. Future studies are needed to explore these associations further in larger populations of individuals with DS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Past studies on sleep and feeding issues also differ from our findings. Unlike previous reports that individuals with DS and other ND conditions like ASD, ADHD, and oppositional defiant disorder have high rates of sleep and feeding problems (Dinkler et al, 2022; Esbensen et al, 2022; Fuemmeler et al, 2020; Reynolds et al, 2019), we did not find significantly higher odds of these issues in our participants with co‐occurring ND and MH conditions. Future studies are needed to explore these associations further in larger populations of individuals with DS.…”
Section: Discussioncontrasting
confidence: 99%
“…Co‐occurring ASD and ADHD diagnoses in our population were based on rigorous diagnostic criteria using a developmental approach in which symptoms and deficits were considered in the context of overall developmental level by clinical experts, and often confirmed with neuropsychological assessments, which may account for why our estimates are lower than some prior reports on prevalence. We also do not conduct routine screening for ADHD with standardized instruments, which may decrease our detection rate; prior studies have shown a difference in detection rate that is dependent on assessment methodology (Esbensen et al, 2022). Given our center's expertise in co‐occurring ND conditions and DS, we may also receive more referrals for diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnostic criteria were developed by reviewing existing formats for the diagnosis of autoimmune encephalitis and encephalopathy (23,24), analysis of existing published phenotypic data in regression in persons with DS and review of previously published and institutional data in cases of established regression (3)(4)(5)(6)(7)(8)10). In addition, data from studies regarding co-morbid non-regression related causes of regression in persons with DS (e.g., autism spectrum disorders) were also reviewed in order to minimize overlapping diagnostic criteria and differentiate cases (17)(18)(19)(20)(21)(22)25). The moderator generated diagnostic criteria were evaluated against an existing DSRD data set prior to release to the panel (26).…”
Section: Development Of Initial Recommendations For Panelmentioning
confidence: 99%
“…People with additional diagnoses have increased likelihood of sleep issues, particularly those with autism (Ballester et al, 2019; Bishop‐Fitzpatrick & Rubenstein, 2019; Elrod & Hood, 2015; Gunes et al, 2019; Köse et al, 2017), attention deficit hyperactivity disorder (Bakke et al, 2021; Chan et al, 2019; Esbensen, Vincent, et al, 2022), dementia or comorbid mental health conditions (Esbensen et al, 2018; Köse et al, 2017), comorbid physical health conditions (Esbensen et al, 2018), physical health conditions known to cause pain (Esbensen et al, 2021; Trickett et al, 2018) and sensory problems including hearing and visual disabilities (Stores, 2019).…”
Section: Resultsmentioning
confidence: 99%